Development of chlorophyll-protein complex nanoparticles for light harvesting and solar cell application. (1st January 2014) - Kondapi, Aneesha; Kishore, Golla; Ahmed, Farhan; Kondapi, Anand K.
Principal components of photosystem involves light reception in plants are chlorophyll protein complexes. In the present study, we have employed chlorophyll protein complexes nanoparticles for photoreception with an aim to assess the excitation like behaviour of these complexes when used in nanoparticle form for the development of photovoltaic devices. As a result of photon interaction with chlorophyll protein complexes initiate electron emission thus convert it into electron deficient centre. Consequently these electrons are transferred to electronic sink 'fullerene nanoparticle', makes it electron efficient, thus providing a natural photocell comprising electron deficient chlorophyll protein complexes nanoparticles as positive electrode and electron efficient fullerene as negative electrode. A comparative analysis of results for different plant species showed significant potential difference in such natural photocells developed with nanoparticles of chlorophyll protein complexes.